THE RELATIONSHIP OF PARENTS USING THERAPEUTIC COMMUNICATION WITH TEMPER TANTRUM BEHAVIOR IN PRESCHOOL CHILDREN AT RT 021 RW 006 SUKAJAYA VILLAGE - Nurhasanah; Nurti Yunika Kristina Gea; Dinda Nur Fajri Hidayati Bunga (Rena Cipta Mandiri, 2024)
Temper tantrum is an outburst of emotion that is out of control and out of control. The signs and symptoms of this temper tantrum vary, ranging from just whining, crying, screaming, rolling on the floor, kicking, hitting. The impact of this temper tantrum is quite dangerous. For example, a child who vents his frustration by rolling on a hard floor can cause injury to the child. According to data from the Indonesian Ministry of Health, the number of children aged 2-4 years in Indonesia who experience temper tantrums is quite large, which is around 19.39 million people. This study aims to determine the relationship between parents using therapeutic communication with temper tantrum behavior in preschool children in RT 021 RW 006 Sukajaya Village. This study used an analytical observational design with a cross sectional design. Sampling using non-probabilty sampling purposive sampling type with a total of 110 respondents. It was found that the results of the Chi Square test had a significant value of 0.045 < a value (0.05). There is a relationship between parents using therapeutic communication with temper tantrum behavior in preschool age children in RT 021 RW 006 Sukajaya Village. There is a relationship between parents using therapeutic communication with temper tantrum behavior in preschool age children in RT 021 RW 006 Sukajaya.